Improving The Writing Ability of The Tenth Year Students of SMK Negeri 3 Parepare Through Story Pyramid Strategy - Yuslinda Yusup (La Parole : Journal of Language Teaching and Pedagogy, 2020)
One of the four English skills which were not taught well at Vocational High School was writing, the students were difficult to write. Based on the researcher’s observation, there were many students who have difficulties in writing. It was proved by the students’ writing score was in fair classification. There were several problems faced by students such as students’ writing was not comprehensible and there were still many errors in vocabulary, grammar, and spelling. Therefore, the researcher intended to help students to overcome their writing difficulties by using story pyramid strategy. This was a good strategy help students to organize their idea or plans before they write a complete paragraph. The objective of the research was to find out whether or not the use of story pyramid strategy can improve the writing ability of the tenth year students of SMKN 3 Parepare. The researcher applied quasi-experimental design with two group pre-test and post-test design. There were two variables; they were independent variable and dependent variable. The samples of the research consisted of 62 students from two classes taken from population of the tenth year students of SMKN 3 Parepare. Class X MM 2 as experimental class and X TKJ 2 as control class. The instrument used in this research was writing test. The result of the data analysis showed that the students’ writing ability improved significantly. It was showed by the mean score of pre-test was 53.16 and the post-test was 77.03 It showed that the use of story pyramid strategy could improve the students’ writing ability of the tenth year students of SMKN 3 Parepare. Beside the different score of pre-test and post-test, the mean score of the students in post-test was higher than the Criteria of Completeness Maximum (75) in SMKN 3 Parepare. After analyzing the data by using SPSS version 21, the result showed the level of significance (0.05) was higher than t-test result (0.000). Those indicated that H1 was accepted and H0 was rejected.